2004
DOI: 10.1158/1078-0432.ccr-0543-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Nuclear Factor-κB and IκBα Proteins in Prostatic Adenocarcinomas

Abstract: Purpose: The nuclear transcription factor nuclear factor-B (NFB) and its inhibitor, IB, regulate the transcription of various genes involved in cell proliferation, adhesion, and survival. The NFB transcription factor complex plays a role in cancer development and progression through its influence on apoptosis. More recently, NFB has been shown to be activated in human and androgen-independent prostate cancer cells. To our knowledge, this is the first study demonstrating the prognostic significance of NFB immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
128
2
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(149 citation statements)
references
References 54 publications
(50 reference statements)
13
128
2
6
Order By: Relevance
“…The prognostic value of RelA is in concordance with studies on prostate cancer, in which both nuclear and cytoplasmic RelA overexpression were linked to disease progression (Fradet et al, 2004;Ross et al, 2004). In gastric adenocarcinoma, the prognostic impact of RelA expression appears to be somewhat conflictive, as overexpression was reported both to be an indicator of adverse (Sasaki et al, 2001;Yamanaka et al, 2004) and favourable (Lee et al, 2005) patient prognosis.…”
Section: Shuklasupporting
confidence: 70%
See 2 more Smart Citations
“…The prognostic value of RelA is in concordance with studies on prostate cancer, in which both nuclear and cytoplasmic RelA overexpression were linked to disease progression (Fradet et al, 2004;Ross et al, 2004). In gastric adenocarcinoma, the prognostic impact of RelA expression appears to be somewhat conflictive, as overexpression was reported both to be an indicator of adverse (Sasaki et al, 2001;Yamanaka et al, 2004) and favourable (Lee et al, 2005) patient prognosis.…”
Section: Shuklasupporting
confidence: 70%
“…Here, we found the NF-kB subunit RelA to be overexpressed in roughly half of a large set of pancreatic adenocarcinomas analysed. Overexpression of cytoplasmic and/or nuclear RelA in tumour tissue has been previously observed in larger study cohorts of gastric (Sasaki et al, 2001;Yamanaka et al, 2004;Cao et al, 2005;Lee et al, 2005), prostate (Fradet et al, 2004;Ismail et al, 2004;Ross et al, 2004; Figure 2 Kaplan -Meier survival curves in dependence of clinicopathological factors and RelA/p65 expression patterns. Overall survival dependent on nodal status (A) and grade (B).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, emerging data obtained from human studies also suggest a potential role of NF-kB in prostate cancer tumorigenesis and/or in its behaviour in a clinical setting (Suh et al, 2002;Lessard et al, 2003;Fradet et al, 2004;Ismail et al, 2004;Ross et al, 2004). In particular, a recent study showed that total overexpression of p65, the best characterised NF-kB protein, was an independent predictor of poor prognosis in prostate cancer patients (Ross et al, 2004). Of note in this study was the fact that nuclear NF-kB expression was not specifically linked with disease relapse.…”
mentioning
confidence: 69%
“…Along this line, several preclinical observations have shown that NF-kB plays a role in prostate cancer growth, survival, angiogenesis and metastatic progression (Muenchen et al, 2000;Yu et al, 2000;Catz and Johnson, 2001;Huang et al, 2001;Gasparian et al, 2002;Gunawardena et al, 2002;Gupta et al, 2002;Suh et al, 2002;Zerbini et al, 2003;Suh and Rabson, 2004). Furthermore, emerging data obtained from human studies also suggest a potential role of NF-kB in prostate cancer tumorigenesis and/or in its behaviour in a clinical setting (Suh et al, 2002;Lessard et al, 2003;Fradet et al, 2004;Ismail et al, 2004;Ross et al, 2004). In particular, a recent study showed that total overexpression of p65, the best characterised NF-kB protein, was an independent predictor of poor prognosis in prostate cancer patients (Ross et al, 2004).…”
mentioning
confidence: 99%